High sensitivity skimmers and non-linear mass dependent fractionation in ICP-MS - Newman, K; Freedman, P; Williams, J; Belshaw, N; Halliday, A (2009)
A number of prototype high sensitivity skimmers have been developed at Nu Instruments. Signal enhancements of up to a factor of 5 were observed, depending on the element and the sampler-skimmer spacing. However, when using these high sensitivity skimmers, the instrumental mass fractionation for neodymium displayed a large non-linear component that could not be corrected for using the accepted mass fractionation laws. It is proposed that the origin of this non-linear mass fractionation is the formation of NdO + close to the skimmer surface. The degree of oxide formation, and hence fractionation, is isotope dependent but it is not a linear function of mass. A decrease in the measured xNd/ 144Nd ratio, relative to standard values, is associated with a concomitant increase in the same ratio in NdO + (and vice versa). The observed inverse relationship between the metal and oxide species is consistent with mass balance calculations. The magnitude of this effect was dependent on conditions at the skimmer surface (geometry, surface coating, etc.) and could be suppressed by the addition of small amounts of N 2 to the carrier gas flow. A simplified energy-resonant ion-atom reaction is postulated to explain these observations, and can be extended to a general model of REE oxide formation in the supersonic expansion. The non-linear fractionation observed also appears to correlate with deviations (from a linear function of mass) in the nuclear charge radii. This is the first evidence of nuclear volume effects contributing to the instrumental mass fractionation in ICP-MS. © The Royal Society of Chemistry.